Những bất cập về hệ thống chính sách khi triển khai dữ liệu mở tại Việt Nam - Phạm, Đức Tiến (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Open data can be known as a type of data that can be accessed, exploited, utilized and edited completely free of charge by anyone without having to seek permission or being licensed to use. In fact, the open data policy system in Vietnam is only managed under the Decree No. 47/2020 of the Government which specified “the stipulation of public agencies in the management, connection and sharing of digital data”. This was the only decree that addressed open data and it was issued on 09/04/2020. The legal framework regulating open data and the issues of accessing, exploiting and applying open data is not really complete and clear, with very few regulatory documents. Meanwhile, open data plays a very important role in supporting the expansion and development of businesses. Thus, it shall create value for society and the digital economy. The article will point out the shortcomings of the legal document system on open data and inadequacies that businesses in Vietnamese businesses may encounter when applying open data for economic development.